Assessing the effectiveness of the United Nations in protecting women and children amidst armed conflicts – a case study of the Russia-Ukraine conflict - Rimšēviča, Elizabete (Riga Graduate School of Law, 2024)
The thesis objectively assesses the effectiveness of the United Nations (UN) in safeguarding women and children during armed conflicts, with emphasis on the conflicts of Bosnia and Ukraine. It examines the institutional frameworks, accountability systems, and political commitments of the UN member states. Finding reveal persistent challenges hindering UN peacekeeping efforts, particularly due to political reluctance among member states. The thesis supports the idea that political commitment is the most significant barrier to fulfilling the UN’s protection mandate. The primary issue lies in the UN Security Council’s (UNSC) incapacity to take effective action, limited by the veto powers and geopolitical rivalries. Recommendations for improvement include UNSC reform to achieve greater transparency and accountability. Despite legal mechanisms, atrocities persist, highlighting the gap between the international ideal perceptions and reality in humanitarian law enforcement.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; armed conflicts; Human rights law; UN Security Council; woman and children; International Humanitarian Law